Composite positive plate, lithium ion battery and preparation method
By using double-layer coating technology of ternary materials and quinone polyimide in the positive electrode sheet of lithium-ion battery, the problem of low safety performance of existing lithium-ion battery positive electrode materials is solved, and higher energy density and better Good safety performance.
Patent Information
- Application Number
- CN202411665889.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-20
AI Technical Summary
While the existing lithium-ion battery positive electrode materials increase the energy density, they have low safety performance, especially the structure of high-nickel ternary lithium batteries is unstable, which can easily lead to safety accidents.
The ternary material and quinone polyimide are used to combine, and the ternary layer and quinone polyimide layer are applied on the foil through double-layer coating technology to form a composite positive electrode sheet to improve the safety performance of the battery.
While maintaining the better electrochemical properties of the ternary materials, the safety performance of the battery is significantly improved, structural stability is enhanced, and safety risks are reduced.
Smart Images

Figure CN119419254A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite positive electrode sheet, a lithium ion battery and a preparation method thereof. Background Art
[0002] Since the invention of lithium-ion batteries, they have attracted widespread attention due to their advantages such as high energy density, long cycle performance, and no memory effect. They have been widely used in transportation, portable devices, aerospace and other fields. In fact, cycle stability, safety, low cost and high energy density are the key factors for the large-scale application of lithium-ion batteries. The key to solving this key problem lies in the electrode material. Currently, commercial lithium-ion battery positive electrode materials mainly include phosphate (LiFePO4), ternary materials (such as LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2、LiNi 0.6 Mn 0.2 Co 0.2 O2、LiNi 0.8 Mn 0.1 Co 0.1 O2), transition metal lithium oxides (LiCoO2, LiMn2O4), etc. Among them, the energy density of ternary lithium is generally 180-230Wh / kg, while the energy density of high-nickel ternary lithium batteries can even reach 250Wh / kg. However, ternary lithium batteries, especially high-nickel ternary lithium batteries, are structurally unstable and have low safety. Almost all of the fire accidents reported in new energy vehicles in recent years are closely related to ternary lithium batteries, so ternary lithium batteries have also been labeled as unsafe. In contrast, lithium iron phosphate has excellent structural stability and higher safety, but the energy density of lithium iron phosphate is generally 140-160Wh / kg, and the current maximum is 180Wh / kg. For the ever-increasing mileage requirements of new energy vehicles, its energy density is obviously too low.
[0003] In recent years, organic materials with redox active sites such as organic free radicals, organic disulfides, carbonyl compounds, etc. have been widely studied. Among them, quinone polyimide, as a typical polycarbonyl polymer, has the characteristics of good thermal stability. In addition, quinone polymers have high theoretical capacity and good reaction reversibility. Therefore, quinone polyimide with two high electrochemical activity characteristics is a safe and high-performance lithium-ion battery electrode material. However, the conductivity of the polymer in the electrolyte is low, so the rate performance is low when used alone as a positive electrode material for lithium-ion batteries.
[0004] The existing positive electrode of lithium-ion batteries usually uses lithium iron phosphate, transition metal oxides, organic polymers or composite materials as active materials, which are then mixed with a certain proportion of conductive carbon black and a binder into a uniform slurry, and then coated on the current collector and cut into positive electrode sheets for lithium-ion batteries. The performance of lithium-ion batteries made by this method has a strong correlation with a single positive electrode material. For example, when a positive electrode sheet made of a single-layer lithium iron phosphate mixed slurry is used as a positive electrode of a lithium-ion battery, the battery has high safety and low energy density; when a positive electrode sheet made of a single-layer nickel cobalt manganese oxide mixed slurry is used as a positive electrode of a lithium-ion battery, the battery has high energy density and low safety performance; when a positive electrode sheet made of a single-layer organic conductive material quinone polyimide mixed slurry is used as a positive electrode of a lithium-ion battery, the battery has high safety performance, poor conductivity, incomplete active sites, and poor rate performance.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a composite positive electrode sheet, a lithium ion battery and a preparation method. By combining a ternary material and a quinone polyimide, a double-layer coating technology is used to simultaneously coat the ternary layer and the quinone polyimide layer on a foil, and then dry and cut the foil to prepare a new double-layer positive electrode sheet. The good electrochemical properties of the ternary material can be maintained while the safety performance of the battery is improved.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] The present invention provides a composite positive electrode sheet, comprising: a current collector, a ternary material layer and a quinone polyimide layer;
[0009] The ternary material layer is located between the current collector and the quinone polyimide layer;
[0010] The quinone polyimide layer includes quinone polyimide and a lithium replenisher.
[0011] Further, on the basis of the above technical solution, the ternary material layer includes 94-98% of the ternary active material, 1-3% of the first conductive agent and 1-3% of the first binder in terms of mass percentage;
[0012] And / or, in terms of mass percentage, the quinone polyimide layer comprises 80-95% quinone polyimide, 1-10% lithium supplement, 2-6% second conductive agent and 2-5% second binder;
[0013] And / or, the current collector is aluminum foil;
[0014] And / or, the thickness of the ternary material layer is 10-180 μm;
[0015] And / or, the thickness of the quinone polyimide layer is 10-180 μm.
[0016] Further, on the basis of the above technical solution, the chemical formula of the ternary active material is LiNi x Co y Mn1 -x-y O2, where 0 <x<1,0<y<1,0<x+y<1;
[0017] and / or, the first conductive agent includes one or more of conductive carbon black, Ketjen black, graphite, graphene, carbon nanotubes, and carbon fibers;
[0018] and / or, the first binder includes one or more of polyvinylidene fluoride, polyaniline, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyvinyl pyrrolidone, polysiloxane, resins, etc.;
[0019] and / or, the second conductive agent includes one or more of conductive carbon black, Ketjen black, graphite, graphene, carbon nanotubes, and carbon fibers;
[0020] and / or, the second binder includes one or more of polyvinylidene fluoride, polyaniline, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyvinyl pyrrolidone, polysiloxane, resins, etc.;
[0021] And / or, the lithium supplement agent includes one or more of a lithium-rich ternary compound, a lithium-rich binary compound, and a composite material based on phase transformation.
[0022] Furthermore, based on the above technical solution, the chemical formula of the lithium-rich ternary compound is Li x M y O z , M is a transition metal, including one of Ni, Fe and Co;
[0023] The lithium-rich binary compound includes one of Li2O, Li2O2, Li2S, Li3P, LiF, and Li3N;
[0024] The phase-inversion-based composite material includes Li2S / N or LiF / N;
[0025] Wherein N includes one of Ni, Co, Mn, Fe and Cu.
[0026] Further, based on the above technical solution, the surface density ratio of the ternary material layer and the quinone polyimide layer is 10:90 to 80:20.
[0027] Further, on the basis of the above technical solution, the quinone polyimide is polymerized from 2,6-diaminoanthraquinone and dianhydride monomers;
[0028] The dianhydride is selected from one or more of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride and naphthalenetetracarboxylic dianhydride.
[0029] The present invention also provides a method for preparing the composite positive electrode sheet as described above, comprising the following steps:
[0030] S1: placing a first binder in a solvent and stirring it, then adding a ternary active material and a first conductive agent and mixing them evenly to obtain a slurry of a ternary material layer;
[0031] S2: placing the second binder in a solvent and stirring it, then adding the quinone polyimide, the lithium supplement agent, and the second conductive agent and mixing them evenly to obtain a slurry of the quinone polyimide layer;
[0032] S3: spraying the slurry of the ternary material layer on the current collector to form a ternary material layer, and then spraying the slurry of the quinone polyimide layer on the ternary material layer to form a quinone polyimide layer;
[0033] S4: Dry, roll, die-cut and cut the coated positive electrode sheet to obtain a high-performance positive electrode sheet.
[0034] Further, based on the above technical solution, the solid content in the slurry of the ternary material layer and the slurry of the quinone polyimide layer is 40-70%;
[0035] And / or, the solvent is N-methylpyrrolidone;
[0036] And / or, the drying temperature is 85-95°C.
[0037] The present invention also provides a lithium ion battery, which comprises the composite positive electrode sheet as described above or the composite positive electrode sheet prepared by the method for preparing the composite positive electrode sheet as described above.
[0038] The present invention also provides a method for preparing a lithium-ion battery, comprising: winding or stacking the composite positive electrode sheet as described above or the composite positive electrode sheet obtained by the method for preparing the composite positive electrode sheet as described above, a separator, and a negative electrode sheet to obtain a core package; and then assembling, baking, injecting, forming, aging, and dividing the capacity to obtain a lithium-ion battery.
[0039] The present invention provides a high-performance composite positive electrode sheet, a lithium-ion battery and a preparation method, which have the following beneficial effects:
[0040] 1. The present invention combines a ternary material with a quinoid polyimide, and uses a double-layer coating technique to simultaneously coat a ternary layer and a quinoid polyimide layer on a foil, followed by drying and cutting to prepare a novel double-layer positive electrode sheet. First, a first binder is dissolved in an organic solvent, and then the ternary material and a first conductive agent are mixed in a certain proportion to form a flowing slurry for making the first positive electrode layer. The ternary material is at least one of LiNi x Co y Mn 1-x-y O2, where 0 < x < 1, 0 < y < 1, 0 < x + y < 1, and this material has a relatively high energy density and rate performance. Then, a second binder is dissolved in an organic solvent, and the quinoid polyimide, a second conductive agent, and a lithium supplement agent are mixed in the glue solution to form a flowing slurry for making the second positive electrode layer. After both slurries are prepared, they are respectively sprayed as the upper and lower layers of the double-layer positive electrode sheet on the foil, and after drying, a double-layer positive electrode sheet is formed. Since the quinoid polyimide has good structural stability and many active sites. However, when used as a positive electrode, it does not contain lithium ions itself, and the formation of the SEI film during the formation process will consume lithium ions in the electrolyte, resulting in the loss of active lithium, reducing the charge-discharge efficiency and energy density of the battery. Therefore, adding a lithium supplement agent to the second positive electrode can compensate for the irreversible lithium loss caused during the formation of the SEI film on the negative electrode. Therefore, by mixing the quinoid polyimide, the lithium supplement agent, the second conductive agent, and the second binder in a certain proportion, dissolving and mixing them in an organic solvent, and then coating them on the ternary material layer to form a physical coating, the electrochemical performance of the ternary material can be maintained while improving the safety performance of the battery.
[0041] 2. Adding a lithium supplement agent to the quinoid polyimide polymer positive electrode slurry can increase the capacity of the battery.
[0042] 3. Different from traditional single-layer electrodes, the double-layer composite electrode is beneficial to giving full play to the advantages of each material, providing an idea for the preparation of the positive electrode sheet of a lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following will briefly introduce the drawings required for use in the description of the specific embodiments or the prior art. Obviously, the following drawings are some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.
[0044] Figure 1 It is a schematic structural diagram of the lithium-ion battery provided by the present invention;
[0045] Figure 2 It is the quinoid polyimide structure and the redox reaction mechanism during the charge-discharge process provided by the present invention;
[0046] icon:
[0047] 1. Copper foil; 2. Graphite; 3. Diaphragm; 4. Quinone polyimide layer; 41. Lithium supplement; 42. Quinone polyimide; 5. Ternary material layer; 51. Ternary material; 6. Aluminum foil. DETAILED DESCRIPTION
[0048] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0049] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0050] According to a first aspect of the present invention, there is provided a composite positive electrode sheet, comprising a current collector, a ternary material layer and a quinone polyimide layer;
[0051] The ternary material layer is located between the current collector and the quinone polyimide layer;
[0052] The quinone polyimide layer includes quinone polyimide and a lithium replenisher.
[0053] Specifically, the ternary material layer is attached to the surface of the current collector, and the quinone polyimide layer is attached to the surface of the ternary material layer. Quinone polyimide is used as an active material, such as Figure 2 As shown in Figure 2, the four carbonyl groups on the polyimide anhydride unit and the two carbonyl groups on the quinone unit can undergo redox reactions with lithium ions, thereby achieving a high concentration of 382.6 mAg -1 Theoretical capacity; although quinone polyimide has multiple active sites, it does not contain lithium ions when used as a positive electrode. When forming the SEI film during the formation process, it will consume lithium ions in the electrolyte, resulting in the loss of active lithium, which reduces the charge and discharge efficiency and energy density of the battery. In order to avoid the loss of lithium ions, the present invention adds a lithium supplement in the second layer of the positive electrode to make up for the irreversible lithium loss caused by the formation of the SEI film with the negative electrode.
[0054] As an optional embodiment of the present invention, the ternary material layer includes, by mass percentage, 94-98% (such as 95%, 96%, 97%, etc.) of the ternary active material, 1-3% (such as 1.5%, 2%, 2.5%, etc.) of the first conductive agent and 1-3% (such as 1.5%, 2%, 2.5%, etc.) of the first binder.
[0055] As an optional embodiment of the present invention, the quinone polyimide layer includes 80-95% (e.g., 82%, 84%, 86%, 88%, 90%, 92%, 94%, etc.) of quinone polyimide, 1-10% (e.g., 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, etc.) of lithium supplement, 2-6% (e.g., 3%, 4%, 5%, etc.) of a second conductive agent, and 2-5% (e.g., 3%, 3.5%, 4%, 4.5%, etc.) of a second binder, by mass percentage;
[0056] Specifically, excessive use of lithium supplements (content greater than 10%) may lead to crystal formation on the surface of the negative electrode, lithium dendrites may pierce the negative electrode and affect safety performance, and the gas generated by the lithium supplement after lithium removal may react with the electrolyte, causing the battery volume to expand, which will also increase the battery production cost.
[0057] As an optional embodiment of the present invention, the current collector is aluminum foil.
[0058] As an optional embodiment of the present invention, the thickness of the ternary material layer is 10-180 μm (such as 20 μm, 50 μm, 70 μm, 100 μm, 120 μm, 140 μm, 160 μm, etc.).
[0059] As an optional embodiment of the present invention, the thickness of the quinone polyimide layer is 10-180 μm (such as 20 μm, 50 μm, 70 μm, 100 μm, 120 μm, 140 μm, 160 μm, etc.).
[0060] As an optional embodiment of the present invention, the ternary active material is a conventional ternary active material in the art, and its chemical formula is LiNi x Co y Mn1 -x-y O2, where 0 <x<1,0<y<1,0<x+y<1;
[0061] The first conductive agent is a conventional conductive agent in the art, typically but not limited to one or more of conductive carbon black, Ketjen black, graphite, graphene, carbon nanotubes, and carbon fibers;
[0062] The first binder is a conventional binder in the art, typically but not limitedly including one or more of polyvinylidene fluoride, polyaniline, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyvinyl pyrrolidone, polysiloxane, resins, and the like.
[0063] The second conductive agent is a conventional conductive agent in the art, typically but not limited to one or more of conductive carbon black, Ketjen black, graphite, graphene, carbon nanotubes, and carbon fibers;
[0064] The second binder is a conventional binder in the art, typically but not limited to one or more of polyvinylidene fluoride, polyaniline, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyvinyl pyrrolidone, polysiloxane, resins, etc.;
[0065] In the present invention, the first conductive agent and the second conductive agent may be the same or different, and the first binder and the second binder may be the same or different.
[0066] The lithium supplement agent is a conventional lithium supplement agent in the art, and typically, but not limitedly, includes one or more of a lithium-rich ternary compound, a lithium-rich binary compound, and a composite material based on phase transformation.
[0067] As an optional embodiment of the present invention, the chemical formula of the lithium-rich ternary compound is Li x M y O z , M is a transition metal, including one of Ni, Fe, and Co; such as Li2NiO2, Li5FeO4, Li6CoO4, etc.;
[0068] The lithium-rich binary compound includes one of Li2O, Li2O2, Li2S, Li3P, LiF, and Li3N;
[0069] The phase-inversion-based composite material includes Li2S / N or LiF / N;
[0070] Wherein N includes one of Ni, Co, Mn, Fe and Cu.
[0071] As an optional embodiment of the present invention, the surface density ratio of the ternary material layer and the quinone polyimide layer is 10:90 to 80:20, more preferably 10:90 to 70:30, such as 30:70, 40:60, 50:50, 60:40, 70:30, etc.
[0072] Specifically, although increasing the content of quinone polyimide can improve the safety performance of the battery, since the theoretical capacity of quinone polyimide as a positive electrode material is lower than that of a ternary material, excessive addition will affect the battery capacity.
[0073] As an optional embodiment of the present invention, the quinone polyimide is polymerized from 2,6-diaminoanthraquinone and dianhydride monomers;
[0074] The dianhydride is selected from one or more of pyromellitic dianhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), and naphthalenetetracarboxylic dianhydride (NTCDA).
[0075] Specifically, an appropriate amount of equimolar 2,6-diaminoanthraquinone and dianhydride monomer are refluxed in an organic solvent N'N-dimethylformamide (DMF) at 170-200°C (such as 170°C, 180°C, 190°C, etc.) for 15-18 hours to obtain an intermediate product, and then the intermediate product is subjected to a high temperature 340-360°C (such as 345°C, 350°C, 355°C) for 7-10 hours to synthesize a quinone polyimide electrode material with redox activity.
[0076] According to a second aspect of the present invention, there is provided a method for preparing the composite positive electrode sheet as described above, comprising the following steps:
[0077] S1: placing a first binder in a solvent and stirring it, then adding a ternary active material and a first conductive agent and mixing them evenly to obtain a slurry of a ternary material layer;
[0078] S2: placing the second binder in a solvent and stirring it, then adding the quinone polyimide, the lithium supplement agent, and the second conductive agent and mixing them evenly to obtain a slurry of the quinone polyimide layer;
[0079] S3: spraying the slurry of the ternary material layer on the current collector to form a ternary material layer, and then spraying the slurry of the quinone polyimide layer on the ternary material layer to form a quinone polyimide layer;
[0080] S4: Dry, roll, die-cut and cut the coated positive electrode sheet to obtain a high-performance positive electrode sheet.
[0081] Specifically, the ternary material layer and the quinone polyimide layer in the present invention are both flowing slurry layers. After the ternary material layer is sprayed, the quinone polyimide layer is directly sprayed on the surface of the undried ternary material layer, and no traditional drying treatment is required in the middle. This continuous and uninterrupted spraying process makes full use of the fluidity of the two layers of materials in a wet state, so that the ternary material layer and the quinone polyimide layer form a tighter and gapless combination at the interface in contact with each other. Compared with the practice in which each layer of material needs to be dried separately before the next layer is coated in the traditional process, the method of the present invention has a faster coating efficiency, significantly improves the interlayer contact quality, reduces the interface gap caused by drying shrinkage, and thus greatly reduces the overall resistance of the pole piece. In addition, since the two layers of material are directly combined in a flowing state, it not only promotes a tighter intermolecular interaction, but also facilitates the efficient migration of ions between material layers. This optimized interlayer structure is crucial to improving the performance of the battery, especially in terms of improving energy density, accelerating charge and discharge rates, and extending cycle life.
[0082] As an optional embodiment of the present invention, the solid content in the slurry of the ternary material layer and the slurry of the quinone polyimide layer are both 40-70% (such as 45%, 50%, 55%, 60%, 65%, etc.).
[0083] The solvent in steps S1 and S2 of the method for preparing a high-performance positive electrode sheet provided by the present invention is a conventional solvent for preparing a positive electrode sheet. Typically, but not limitedly, the solvent is selected from N-methylpyrrolidone (NMP).
[0084] As an optional embodiment of the present invention, the drying temperature is 85-95°C (such as 87°C, 90°C, 92°C, 94°C, etc.), preferably 90°C.
[0085] According to a third aspect of the present invention, a lithium-ion battery is provided, wherein the lithium-ion battery comprises the composite positive electrode sheet as described above.
[0086] Specifically, Figure 1 As shown, the lithium-ion battery includes a negative electrode sheet, a separator 3 and a positive electrode sheet, wherein the current collector of the negative electrode sheet is a copper foil 1, and the active material in the negative electrode sheet is graphite 2; the positive electrode sheet is a composite positive electrode sheet as described above, and its current collector is an aluminum foil 6, on which a ternary material layer 5 is coated, and the ternary material layer 5 contains a ternary material 51, and on the ternary material layer 5, a quinone polyimide layer 4 is coated, and the quinone polyimide layer 4 contains a lithium supplement 41 and a quinone polyimide 42.
[0087] According to a fourth aspect of the present invention, there is provided a method for preparing the lithium-ion battery as described above, comprising: winding or stacking the composite positive electrode sheet, separator, and negative electrode sheet to obtain a core package; and then assembling, baking, injecting, forming, aging, and dividing the capacity to obtain a lithium-ion battery.
[0088] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.
[0089] First of all, it is necessary to explain the synthesis method of the quinone polyimide polymer used in the following examples and comparative examples:
[0090] Take an appropriate amount of equimolar 2,6-diaminoanthraquinone and anhydride units (such as pyromellitic acid dianhydride) and dissolve them in an organic solvent N'N-dimethylformamide (DMF), then reflux at 180°C for 16 hours under argon protection to obtain an intermediate product, and then the intermediate product is subjected to a high temperature of 350°C and argon protection for 8 hours to undergo a ring-closing reaction to synthesize a quinone-type polyimide electrode material with redox activity. The lithium storage process is as follows: Figure 2 shown.
[0091] Ternary materials and other adhesives and conductive agents are currently commercially available materials.
[0092] Example 1
[0093] (1) The ternary material NCM622 (LiNi 0.6 Co 0.2 Mn 0.2 O2), conductive carbon black SP, conductive carbon nanotubes CNT, and binder PVDF are prepared in a mass ratio of 96wt%: 2wt%: 0.5wt%: 1.5wt%, PVDF is dissolved in NMP and then the other components are evenly mixed in the PVDF glue, the solid content in the ternary slurry is 60%, and a slurry of the ternary material layer is obtained.
[0094] (2) Prepare quinone polyimide PI, lithium supplement Li5FeO4, conductive carbon black SP, and binder PVDF in a mass ratio of 90wt%: 2wt%: 6wt%: 2wt%, dissolve PVDF in NMP, and evenly mix the other components in the PVDF glue solution. The content of the solid component in the polymer slurry accounts for 60%, and obtain a slurry of the quinone polyimide layer.
[0095] (3) Then the slurry of the ternary material layer is sprayed on one side of the aluminum foil, and then the slurry of the quinone polyimide layer is sprayed on the ternary material layer to form a composite positive electrode sheet in which the quinone polyimide physically coats the ternary layer. The surface density of the ternary layer is 210g / m 2 , with a thickness of 78 μm. The surface density of the quinone polyimide layer is 90 g / cm 2The thickness is 46 μm. The density ratio of the ternary material layer and the quinone polyimide layer is 70:30.
[0096] (4) The coated positive electrode sheet is then dried in an oven at 90°C, and then rolled, die-cut, and slit to form a double-layer positive electrode sheet of a ternary material and a quinone polymer. The positive electrode sheet, the separator, and the negative electrode sheet are then wound or stacked to obtain a core package, which is then assembled, baked, injected, formed, aged, and divided to obtain a lithium-ion battery.
[0097] Embodiment 2-4
[0098] The main difference between Examples 2 to 4 and Example 1 is that the surface density ratio of the ternary material layer and the quinone polyimide layer is adjusted to 50:50 (the surface density of the ternary material layer is 150 g / m 2 , thickness is 55.7 μm, and the surface density of the quinone polyimide layer is 150 g / cm 2 , thickness is 76.7μm), 30:70 (the surface density of the ternary material layer is 90g / m 2 , thickness is 33.4 μm, and the surface density of the quinone polyimide layer is 210 g / cm 2 , thickness is 107.3μm) and 10:90 (the surface density of the ternary material layer is 30g / m 2 , thickness is 11.1 μm, and the surface density of the quinone polyimide layer is 270 g / cm 2 , thickness is 138.0μm).
[0099] Example 5
[0100] (1) The ternary material NCM811 (LiNi 0.8 Co 0.1 Mn 0.1 O2), conductive carbon black SP, conductive carbon nanotubes CNT, and binder PVDF are prepared in a mass ratio of 96wt%: 2wt%: 0.5wt%: 1.5wt%, PVDF is dissolved in NMP and then other components are evenly mixed in the PVDF glue, and the content of solid components in the ternary slurry accounts for 60%.
[0101] (2) Prepare quinone polyimide PI, lithium supplement Li5FeO4, conductive carbon black SP, and binder PVDF in a mass ratio of 90wt%: 2wt%: 6wt%: 2wt%, dissolve PVDF in NMP, and evenly mix the other components in the PVDF glue solution, with the solid component accounting for 60% of the polymer slurry.
[0102] (3) Then the slurry of the ternary material layer is sprayed on one side of the aluminum foil, and then the slurry of the quinone polyimide layer is sprayed on the ternary material layer to form a composite positive electrode sheet in which the quinone polyimide physically coats the ternary layer. The surface density ratio of the ternary material layer and the quinone polyimide layer is 70:30. The surface density of the ternary layer is 210g / m 2 , with a thickness of 78 μm. The surface density of the quinone polyimide layer is 90 g / cm 2 , thickness is 46μm.
[0103] (4) The coated positive electrode sheet is then dried in an oven at 90°C, and then rolled, die-cut, and slit to form a double-layer positive electrode sheet of ternary materials and quinone polymer. The positive electrode sheet, separator, and negative electrode sheet are then wound or stacked to obtain a core package, and then assembled, baked, injected, formed, aged, and divided to obtain a lithium-ion battery.
[0104] Example 6
[0105] (1) The ternary material NCM622 (LiNi 0.6 Co 0.2 Mn 0.2 O2), conductive carbon black SP, conductive carbon nanotubes CNT, and binder PVDF are prepared in a mass ratio of 96wt%: 2wt%: 0.5wt%: 1.5wt%, PVDF is dissolved in NMP and then the other components are evenly mixed in the PVDF glue, and the solid content in the ternary slurry is 60%.
[0106] (2) Prepare quinone polyimide PI, lithium supplement Li3N, conductive carbon black SP, and binder PVDF in a mass ratio of 90wt%: 2wt%: 6wt%: 2wt%, dissolve PVDF in NMP, and evenly mix the other components in the PVDF glue solution, with the solid component accounting for 60% of the polymer slurry.
[0107] (3) Then the slurry of the ternary material layer is sprayed on one side of the aluminum foil, and then the slurry of the quinone polyimide layer is sprayed on the ternary material layer to form a composite positive electrode sheet in which the quinone polyimide physically coats the ternary layer. The surface density of the ternary layer is 210g / m 2 , with a thickness of 78 μm. The surface density of the quinone polyimide layer is 90 g / cm 2 The thickness is 46 μm. The density ratio of the ternary material layer and the quinone polyimide layer is 70:30.
[0108] (4) The coated positive electrode sheet is then dried in an oven at 90°C, and then rolled, die-cut, and slit to form a double-layer positive electrode sheet of a ternary material and a quinone polymer. The positive electrode sheet, the separator, and the negative electrode sheet are then wound or stacked to obtain a core package, which is then assembled, baked, injected, formed, aged, and divided to obtain a lithium-ion battery.
[0109] Example 7
[0110] The operating steps and technical parameters in Example 7 are the same as those in Example 6, the main difference being that the mass ratio of quinone polyimide PI, lithium supplement Li3N, conductive carbon black SP and binder PVDF is 87wt%:5wt%:6wt%:2wt%.
[0111] Comparative Example 1
[0112] The main difference between this comparative example and Example 1 is that only a ternary material layer is coated on the aluminum foil, specifically:
[0113] The ternary material NCM622 (LiNi 0.6 Co 0.2 Mn 0.2 O2), conductive carbon black SP, conductive carbon nanotubes CNT, and binder PVDF are prepared in a mass ratio of 96wt%: 2wt%: 0.5wt%: 1.5wt%, PVDF is dissolved in NMP, and the other components are evenly mixed in the PVDF glue, and then coated on aluminum foil to form an active material layer, and then the coated positive electrode sheet is dried in an oven at 90°C, and then rolled, die-cut, and slit to form a positive electrode sheet, wherein the thickness of the active material layer is 114.3μm and the surface density is 300g / m 2 The positive electrode sheet, the separator and the negative electrode sheet are then wound or stacked to obtain a core package, and then assembled, baked, injected, formed, aged, and divided into different volumes to obtain a lithium-ion battery.
[0114] Comparative Example 2
[0115] The main difference between this comparative example and Example 1 is that only a quinone polyimide layer is coated on the aluminum foil, specifically:
[0116] Prepare quinone polyimide PI, lithium supplement Li2NiO2, conductive carbon black SP, and binder PVDF in a mass ratio of 90wt%: 2wt%: 6wt%: 2wt%, dissolve PVDF in NMP, and evenly mix the other components in the PVDF glue. The solid component accounts for 60% of the polymer slurry. Then apply it directly on the aluminum foil to form an active material. Then dry the coated positive electrode sheet in an oven at 90°C, and then roll, die-cut, and slit to make a positive electrode sheet, in which the thickness of the active material layer is 153.3μm and the surface density is 300g / m2 The positive electrode sheet, the separator and the negative electrode sheet are then wound or stacked to obtain a battery cell, and the battery cell is then baked, injected, formed, aged, and divided to obtain a lithium-ion battery.
[0117] Comparative Example 3
[0118] The main difference between this comparative example and Example 1 is that the quinone polyimide layer does not contain a lithium supplementing agent, specifically:
[0119] (1) The ternary material NCM622 (LiNi 0.6 Co 0.2 Mn 0.2 O2), conductive carbon black SP, conductive carbon nanotubes CNT, and binder PVDF are prepared in a mass ratio of 96wt%: 2wt%: 0.5wt%: 1.5wt%, PVDF is dissolved in NMP, and the other components are evenly mixed in PVDF glue, and then coated on one side of the aluminum foil to form a ternary material layer. The solid component accounts for 60% of the ternary slurry.
[0120] (2) Prepare quinone polyimide PI, conductive carbon black SP, and binder PVDF in a mass ratio of 92wt%: 6wt%: 2wt%, dissolve PVDF in NMP, and evenly mix the other components in the PVDF glue, and then apply it on top of the ternary material layer to form a quinone polyimide layer. The content of solid components in the polymer slurry accounts for 60%. The surface density ratio of the ternary material layer and the quinone polyimide layer is 70:30. Then, after the coated positive electrode sheet is dried in an oven at 90°C, it is rolled, die-cut, and slit to form a double-layer positive electrode sheet of ternary material and quinone polymer, in which the surface density of the ternary material layer is 210g / m 2 , with a thickness of 78 μm. The surface density of the quinone polyimide layer is 90 g / cm 2 The positive electrode sheet, the separator and the negative electrode sheet are then wound or stacked to obtain a battery cell, and the battery cell is then baked, injected, formed, aged, and divided to obtain a lithium-ion battery.
[0121] Comparative Example 4
[0122] The main difference between this comparative example and Example 1 is that the density ratio of the ternary material layer to the quinone polyimide layer is 90:10 (wherein the density of the ternary material layer is 270 g / m 2 , thickness is 100.3μm, density of quinone polyimide layer is 30g / m 2 , thickness is 15.3 μm), and the remaining operation steps and technical parameters are the same as those in Example 1.
[0123] Comparative Example 5
[0124] The main difference between this comparative example and Example 1 is that the ternary material slurry layer is dried after spraying, and then the quinone polyimide layer is sprayed, and the remaining operation steps and technical parameters are the same as those of Example 1. Specifically:
[0125] (1) The ternary material NCM622 (LiNi 0.6 Co 0.2 Mn 0.2 O2), conductive carbon black SP, conductive carbon nanotubes CNT, and binder PVDF are prepared in a mass ratio of 96wt%: 2wt%: 0.5wt%: 1.5wt%, PVDF is dissolved in NMP and then the other components are evenly mixed in the PVDF glue, the solid content in the ternary slurry is 60%, and a slurry of the ternary material layer is obtained.
[0126] (2) Prepare quinone polyimide PI, lithium supplement Li5FeO4, conductive carbon black SP, and binder PVDF in a mass ratio of 90wt%: 2wt%: 6wt%: 2wt%, dissolve PVDF in NMP, and evenly mix the other components in the PVDF glue solution. The content of the solid component in the polymer slurry accounts for 60%, and obtain a slurry of the quinone polyimide layer.
[0127] (3) Then the slurry of the ternary material layer is sprayed on one side of the aluminum foil and dried, and then the slurry of the quinone polyimide layer is sprayed on the ternary material layer to form a composite positive electrode sheet with the quinone polyimide physically coated with the ternary layer. The surface density of the ternary layer is 210g / m 2 , with a thickness of 78 μm. The surface density of the quinone polyimide layer is 90 g / cm 2 The thickness is 46 μm. The density ratio of the ternary material layer and the quinone polyimide layer is 70:30.
[0128] The coated positive electrode sheet is then dried in an oven at 90°C, and then rolled, die-cut, and slit to form a double-layer positive electrode sheet of a ternary material and a quinone polymer. The positive electrode sheet, separator, and negative electrode sheet are then wound or stacked to obtain a core package, which is then assembled, baked, injected, formed, aged, and divided into volumes to obtain a lithium-ion battery.
[0129] Performance Testing
[0130] In order to test the performance of the positive electrode sheets obtained in the examples and comparative examples, the positive electrode sheets obtained in the examples and comparative examples were respectively assembled into batteries with negative electrode sheets, separators and electrolytes, wherein:
[0131] Preparation of negative electrode:
[0132] The mass percentages of graphite, binder styrene-butadiene rubber SBR, thickener sodium carboxymethyl cellulose CMC, and conductive agent super P are set to be 95.5wt%, 1.7wt%, 1.8wt%, and 1wt%, respectively.
[0133] Add the binder to deionized water and stir to dissolve. Then add graphite and conductive agent according to the set percentage, stir and disperse evenly, then add thickener and continue stirring to obtain a negative electrode slurry with good dispersion and a slurry solid content of 60%. The slurry is coated on the surface of the current collector copper foil and dried at 90°C. Then the pole piece is rolled, trimmed, cut and stripped. After stripping, it is dried at 110°C for 5 hours under vacuum conditions, and then the pole ears are welded to make a negative electrode sheet. The surface density of the negative electrode sheet is 185g / m 2 , thickness is 130.5μm.
[0134] The separator was a commercially available porous PE (polyethylene) film with a thickness of 16 μm.
[0135] Preparation of electrolyte: Lithium hexafluorophosphate (LiPF6) was dissolved in a mixed solvent consisting of ethyl methyl carbonate (EMC), ethylene carbonate (EC), and dimethyl carbonate (DEC) (the mass ratio of the three was 1:1:1) to obtain an electrolyte with a concentration of 1 mol / L.
[0136] Preparation of the battery:
[0137] The positive electrode sheet, the separator and the negative electrode sheet prepared in the above embodiments and comparative examples are wound into a battery cell, the separator is located between the positive electrode sheet and the negative electrode sheet, the positive electrode is spot-welded with an aluminum tab, and the negative electrode is spot-welded with a nickel tab; then the battery cell is placed in an aluminum-plastic packaging bag, the above electrolyte is injected, and after packaging, formation, capacity division and other processes, a lithium-ion battery with a capacity of 3000mAh is made.
[0138] Performance Testing Methods
[0139] (1) Test of double-layer electrode capacity in grams: The lithium-ion batteries prepared in the above embodiments and comparative examples were charged to 4.3 V at a constant current and voltage of 0.33 C at room temperature (25±2° C.), and then discharged to 2.75 V at 0.33 C. The charge and discharge cycle was repeated three times, and the average discharge capacity in grams of the positive electrode material was calculated for the three times.
[0140] (2) Needle puncture test: The battery cell is discharged at 1C constant current to 2.75V at 25±2℃; let it stand for 30min; charge at 1C constant current and constant voltage to 4.3V, let it stand for 30min; put the battery in a fixture and place it in a fume hood, and use a 5mm diameter rust-free steel needle at a speed of 20-40mm / s and a penetration force of 150-200KG to penetrate the center of the largest surface of the battery at a speed of 20-40mm / s and a penetration force of 150-200KG (the steel needle stays in the battery). Pierce the center of the largest surface of the battery; observe for 1h and record the battery status.
[0141] Performance data
[0142] The performance data of the positive electrode sheets and lithium-ion batteries prepared in Examples 1-7 and Comparative Examples 1-5 are shown in Table 1:
[0143] Table 1
[0144]
[0145]
[0146] As shown in Table 1, compared with Example 1, since in Comparative Example 1, only the ternary material layer is coated on the aluminum foil without the quinone polyimide layer, although the gram capacity of the double-layer electrode is improved, the lithium-ion battery prepared in Comparative Example 1 catches fire and explodes in the puncture test due to the instability of the ternary material.
[0147] As shown in Table 1, compared with Example 1, in Comparative Example 2, only the quinone polyimide layer is coated on the aluminum foil, and no ternary material layer is coated, resulting in a significant decrease in the gram capacity of the double-layer electrode of the prepared lithium ion battery.
[0148] As shown in Table 1, compared with Example 1, since the quinone polyimide layer in Comparative Example 3 does not contain a lithium supplement, when the quinone polyimide forms an SEI film during the chemical formation process, lithium ions are lost, resulting in a significant decrease in the gram capacity of the double-layer electrode of the prepared lithium ion battery.
[0149] As shown in Table 1, compared with Example 1, in Comparative Example 4, since the density ratio of the ternary material layer and the quinone polyimide layer in Comparative Example 4 is 90:10, the content of ternary material in the composite positive electrode sheet is relatively high, resulting in the lithium ion battery prepared in Comparative Example 1 catching fire and exploding in the puncture test.
[0150] As shown in Table 1, compared with Example 1, in Comparative Example 5, the ternary material slurry layer is sprayed and then dried, and then the quinone polyimide layer is sprayed. The interface compatibility between the ternary layer and the quinone polyimide layer is reduced, and the contact impedance between the material layers is increased, which affects the ion migration efficiency between the material layers, resulting in a significant decrease in the gram capacity of the double-layer electrode of the prepared lithium ion battery.
[0151] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A composite positive electrode sheet, characterized in that: include: Current collector, ternary material layer and quinone polyimide layer; The ternary material layer is located between the current collector and the quinone polyimide layer; The quinone polyimide layer includes quinone polyimide and a lithium replenisher.
2. The composite positive electrode sheet according to claim 1, characterized in that: In terms of mass percentage, the ternary material layer includes 94-98% of the ternary active material, 1-3% of the first conductive agent and 1-3% of the first binder; And / or, in terms of mass percentage, the quinone polyimide layer comprises 80-95% quinone polyimide, 1-10% lithium supplement, 2-6% second conductive agent and 2-5% second binder; And / or, the current collector is aluminum foil; And / or, the thickness of the ternary material layer is 10-180 μm; And / or, the thickness of the quinone polyimide layer is 10-180 μm.
3. The composite positive electrode sheet according to claim 2, characterized in that: The chemical formula of the ternary active material is LiNi x Co y Mn1 -x-y O2, where 0 <x<1,0<y<1,0<x+y<1; and / or, the first conductive agent includes one or more of conductive carbon black, Ketjen black, graphite, graphene, carbon nanotubes, and carbon fibers; and / or, the first binder includes one or more of polyvinylidene fluoride, polyaniline, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyvinyl pyrrolidone, polysiloxane, resins, etc.; and / or, the second conductive agent includes one or more of conductive carbon black, Ketjen black, graphite, graphene, carbon nanotubes, and carbon fibers; and / or, the second binder includes one or more of polyvinylidene fluoride, polyaniline, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyvinyl pyrrolidone, polysiloxane, resins, etc.; And / or, the lithium supplement agent includes one or more of a lithium-rich ternary compound, a lithium-rich binary compound, and a composite material based on phase transformation.
4. The composite positive electrode sheet according to claim 3, characterized in that: The chemical formula of the lithium-rich ternary compound is Li x M y O z , M is a transition metal, including one of Ni, Fe and Co; The lithium-rich binary compound includes one of Li2O, Li2O2, Li2S, Li3P, LiF, and Li3N; The phase transformation-based composite material includes Li2S / N or LiF / N, wherein N includes one of Ni, Co, Mn, Fe, and Cu.
5. The composite positive electrode sheet according to claim 1, characterized in that: The surface density ratio of the ternary material layer to the quinone polyimide layer is 10:90 to 80:
20.
6. The composite positive electrode sheet according to claim 2, characterized in that: The quinone polyimide is polymerized from 2,6-diaminoanthraquinone and dianhydride monomers; The dianhydride is selected from one or more of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride and naphthalenetetracarboxylic dianhydride.
7. A method for preparing a composite positive electrode sheet according to any one of claims 1 to 6, characterized in that: The steps include: S1: placing a first binder in a solvent and stirring it, then adding a ternary active material and a first conductive agent and mixing them evenly to obtain a slurry of a ternary material layer; S2: placing the second binder in a solvent and stirring it, then adding the quinone polyimide, the lithium supplement agent, and the second conductive agent and mixing them evenly to obtain a slurry of the quinone polyimide layer; S3: spraying the slurry of the ternary material layer on the current collector to form a ternary material layer, and then spraying the slurry of the quinone polyimide layer on the ternary material layer to form a quinone polyimide layer; S4: Dry, roll, die-cut and cut the coated positive electrode sheet to obtain a high-performance positive electrode sheet.
8. The method for preparing a composite positive electrode sheet according to claim 7, characterized in that: The solid content of the slurry of the ternary material layer and the slurry of the quinone polyimide layer is 40-70%; And / or, the solvent is N-methylpyrrolidone; And / or, the drying temperature is 85-95°C.
9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the composite positive electrode sheet as described in any one of claims 1 to 6 or a composite positive electrode sheet prepared by the method for preparing the composite positive electrode sheet as described in any one of claims 7 to 8.
10. A method for preparing a lithium ion battery as claimed in claim 9, characterized in that: include: The composite positive electrode sheet as described in any one of claims 1 to 6 or the composite positive electrode sheet preparation method as described in any one of claims 7 to 8, the separator, and the negative electrode sheet are wound or stacked to obtain a core package; and then assembled, baked, injected, formed, aged, and divided into volumes to obtain a lithium-ion battery.
Citation Information
Patent Citations
Pole piece used for ternary material lithium ion battery anode and its coating method
CN102412388A
Preparation method of symmetrical polymer-based electrode lithium ion total battery
CN112952204A
Polyimide-coated lithium ion battery positive electrode material, preparation method and application
CN116914101A
Pole piece, preparation method thereof and lithium ion battery
CN117080365A
Double-layer positive plate, preparation method thereof and lithium ion battery
CN117219756A
Cited By
Preparation method of high-temperature-resistant lithium battery cell
CN120767287A
Lithium magnesium phosphate modified positive pole piece, preparation method thereof and lithium ion battery
CN121011624A